A review of direct-to-device satellite technology in bridging connectivity gaps in Malaysia - Mohd Hassan, Siti Maisurah; Roslee, Mardeni; Mohd Marzuki, Azah Syafiah (International Journal of Advances in Applied Sciences, 2025)
The connectivity gap in rural and remote regions of Malaysia remains a significant challenge due to the high costs and technical challenges of deploying fixed-line infrastructure like fiber optics and copper cables. Similarly, expanding cellular networks such as 4G and 5G to these areas is often economically unfeasible for mobile network operators (MNOs) due to low returns on investment. Direct-to-device (D2D) satellite technology has recently emerged as a promising solution, gaining interest from both industry and academia. D2D enables direct communication with standard mobile phones and internet of things (IoT) devices, extending coverage to underserved regions without requiring extensive ground infrastructure. This paper provides a comprehensive overview of D2D technology, its technical aspects, and its suitability as a complementary solution to terrestrial networks. This paper also discusses how D2D technology can bridge the connectivity gap in Malaysia, offering a possible solution to enhance digital inclusion in rural and remote communities.